Biomarkers of Platelet Activation and Their Prognostic Value in Patients With Sepsis-Associated Disseminated Intravascular Coagulopathy - Wegrzyn, Gracelene; Walborn, Amanda; Rondina, Matthew; Fareed, Jawed; Hoppensteadt, Debra (Clinical and applied thrombosis/hemostasis, 2021)
Sepsis-associated disseminated intravascular coagulation (DIC) is related to marked hemostatic changes such as transient thrombocytopenia secondary to the endogenous activation and consumption of platelets. This study measured markers of platelet function in 103 adult ICU patients with clinically established sepsis-associated DIC to determine the biomarker association with disease severity. Patients were categorized as having no DIC, nonovert DIC, or overt DIC using the International Society of Thrombosis and Hemostasis scoring system. Plasma levels of CD40L, platelet factor 4 (PF4), platelet-derived microparticles, and microparticle-associated tissue factor were quantified. Markers of platelet activation were significantly elevated in patients with DIC compared to healthy individuals. This increase was independent of platelet count. Levels of PF4 differed based on the severity of DIC and differentiated nonsurvivors and survivors. These findings suggest that the markers of platelet activation in DIC may not be regulated by the number of circulating platelets and may be independent of the factors leading to their consumption.